Kemampuan Memahami Wacana Lisan Dalam Dialog Interaktif Menggunakan Media Rekaman Pada Siswa SMPS Muhammadiyah Ende - Maria Floriana Serlin; zaenab Jamaludin (research, training and philanthropy institution Natural Aceh, 2021)
Abstract: This study aims to determine the ability to understand oral discourse in interactive dialogue using recording media in class VII students of SMPS Muhammadiyah Ende, Ende Utara District, Ende Regency in the 2019/2020 academic year. The specific purpose of this writing is that researchers know the ability to understand oral discourse in interactive dialogue using recording media in class VII students of private SMP Muhammadiyah Ende, Ende Utara District, Ende Regency. The approach used in this research is a quantitative approach. Data were collected using the instrument test method. Data collection techniques using test techniques. The theory used by the writer is listening skill theory and learning evaluation theory.The results of the data analysis show that students can understand oral discourse in interactive dialogue using recorded media. Their ability is classified as good with the average value obtained is 76.96%. Students who are able to get a value of> 75 with a percentage of 84.31% with a good predicate and students who are unable to get a value of <75 with a percentage of 15.69% with a sufficient predicate. Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan memahami wacana lisan dalam dialog interaktif menggunakan media rekaman pada siswa kelas VII SMPS Muhammadiyah Ende Kecamatan Ende Utara Kabupaten Endetahun pembelajaran 2019/2020. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kuantitatif. Data dikumpulkan dengan menggunakan metode tes esay. Setelah data dikumpulkan selanjutnya data dianalisis dengan menggunakan teknik statistik menggunakan rumus yang dikemukakan oleh Rikwan & Akdon (2010:28). Hasil analisis data menunjukkan bahwa siswa dapat memahami wacana lisan dalam dialog interaktif menggunakan media rekaman. Kemampuan mereka tergolong baik dengan nilai rata-rata yang diperoleh adalah 76,96%. Siswa yang mampu memperoleh nilai > 75 dengan persentase 84,31% dengan predikat baik dan siswa yang tidak mampu memperoleh nilai < 75 dengan persentase 15,69% dengan predikat cukup.